IMMUNO-MODULATORY EFFECTS OF LACTOBACILLUS IN SALMONELLA GALLINARUM INFECTED BROILER CHICKS (Pakistan Journal of Science, 2022)
Lactobacillus is a direct fed microbial which helps to protect organisms against pathogens by discouraging their colonization in intestine. This project had been designed to evaluate the effect of Lactobacillus in broiler chicken experimentally infected with S. gallinarum. A total of 100 day old chicks divided into 4 equal groups (A, B, C & D) comprising 25 chicks in each group. Birds of groups B and D were infected with S. gallinarum orally at day 19th of age. Group A was kept as control negative and group C and D were supplemented with Lactobacillus. Disease combat efficiency in each group was determined by monitoring weight gains, morbidity & mortality rates, immune parameters and histopathological findings. Analysis of variance (ANOVA) technique was used to compare results by using MSTAT C statistical software. The results revealed that morbidity and mortality rates were more in group B and significantly low in group C (Lactobacillus supplemented) and D (Treatment group). The antibody response was found to be highest in group C followed by group D. Body weight gains and relative organ weight gains were also higher in treated groups with maximum in the group C followed by group D. Histopathology studies revealed that treated groups showed less lesions and untreated infected group showed all classical lesions of the disease. The study concluded that Lactobacillus can be very efficient as probiotic for prophylactic immune-stimulation to replace antibiotics being used irrationally as prophylaxis.
Keywords: Immuno-modulatory; Lactobacillus; Probiotics; Salmonella gallinarum; Broiler chicks